Servqual Model as Performance Evaluation Instrument for Small and Medium Sized Enterprises (SME): Evidence From Customers in Nigeria - Obioma,H, Onyeaghala, (European Scientific Journal, ESJ, 2016)
It is the intention of this study to ascertain if SERVQUAL model can serve as an instrument for measuring performance of small and medium scale enterprises in Nigeria. The study adopted the Kano model as the theoretical framework. Empirical works on service quality and customer satisfaction were reviewed. Survey research design was adopted and conducted with the use of structured questionnaire designed in a 5 point likert scale format ranging from strongly agree, agree, strongly disagree, disagree and undecided. Twelve (12) small and medium scale enterprises operating in six geo-political zones of Nigeria were judgmentally selected, from where a sample of 60 was drawn using Taro Yamane formula. The questionnaire was validated and its reliability established. Data presentation and analysis was carried out using tables and simple percentages. Chi-square statistic; a nonparametric technique was employed in the test of the three hypotheses formulated to guide the study. This led to rejection of the three null hypotheses indicating that: Service quality dimensions has relationship with performance of small and medium scale enterprises; tangibility, reliability, responsiveness, assurance and empathy services can be used to measure performance of small and medium scale enterprises. This justifies that SERVQUAL dimensions; tangibility, reliability, responsiveness, assurance and empathy are indicators of customer satisfaction, implying that they can be employed as performance evaluation tools for small and medium scale enterprises. It is recommended that small and medium scale enterprises should direct their operations in line with SERVQUAL dimensions, if they want to achieve customer satisfaction and business performance.